Therapeutic effects of tyroserleutide on lung metastasis of human hepatocellular carcinoma SK-HEP-1 and its mechanism affecting ICAM-1 and MMP-2 and -9 - Che X (Drug Design, Development and Therapy, 2018)
Xuchun Che,1,* Rong Lu,1,2,* Zheng Fu,2 Yajun Sun,3 Zhi-feng Zhu,2 Jin-ping Li,2 Song Wang,2 Jing Jia,2 Qing Wang,4 Zhi Yao1 1Department of Immunology, Tianjin Key Laboratory of Cellular and Molecular Immunology, Key Laboratory of Educational Ministry of China, School of Medical Sciences, Tianjin Medical University, Tianjin, People’s Republic of China; 2Department of Drug Development, Tianjin Kangzhe Pharmaceutical Company, Ltd., Tianjin, People’s Republic of China; 3Department of Blood Transfusion, General Hospital, Tianjin Medical University, Tianjin, People’s Republic of China; 4Department of Clinical Laboratory, General Hospital, Tianjin Medical University, Tianjin, People’s Republic of China *These authors contributed equally to this work Background: Tyroserleutide (YSL) inhibits the growth and metastasis of human hepatocellular carcinoma (HCC). This paper studied the effect of YSL on metastasis of human HCC and investigated its mechanisms. Methods: In vivo, experimental lung metastasis models of human HCC SK-HEP-1 cells in nude mice were established, and In vitro, the proliferation, adhesion and invasion of SK-HEP-1 cells were detected. Results: In vivo, YSL significantly inhibited the metastasis of human HCC. In vitro, YSL significantly inhibited the proliferation, adhesion and invasion of SK-HEP-1 cells. Through analyses with reverse transcription PCR (RT-PCR) and Western blot, we observed that YSL significantly inhibited the expressions of ICAM-1 in SK-HEP-1 cells. Through RT-PCR, Western blot and zymography methods, YSL was discovered to decrease the mRNA level, protein expression and activity of MMP-2 and -9 in SK-HEP-1 cells. Conclusion: We concluded that YSL could inhibit tumor growth and metastasis of human HCC SK-HEP-1 cells. Keywords: proliferation, adhesion, invasion, ICAM-1, MMP-2, MMP-9